2020
DOI: 10.3390/su12166309
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Tongue Kissing in Hook-Ups after COVID-19

Abstract: A growing body of social and behavioral sciences studies are providing evidence on how COVID-19 is influencing changes in society and among individuals. A few of those studies focus on how it is affecting behavioral and habit changes in stable couples. Yet its influence on changes in hook-ups remains understudied. To contribute to filling this gap, this exploratory study analyzes changes related to tongue kissing in hook-ups promoted by increased awareness of tongue kissing certain people as a potential source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…In sexual-affective relations, coercion can occur both in verbal and non-verbal communication, and, therefore, the solution is necessarily based on taking into account not only speech acts, which are essential, but also other types of communicative acts (Flecha et al, 2020 ). The coercive dominant discourse imposes the link between attraction and violence, influencing the socialization that occurs from birth, in settings such as school, family, circles of friends, and audiovisual products, and therefore prevention is necessary in all of these settings (Aiello et al, 2018 ; Rios-Gonzalez et al, 2018 , 2019 ; Ruiz-Eugenio et al, 2020 ; Villarejo et al, 2020 ).…”
Section: Language and Discourses On Non-hegemonic Masculinities And Self-confidencementioning
confidence: 99%
“…In sexual-affective relations, coercion can occur both in verbal and non-verbal communication, and, therefore, the solution is necessarily based on taking into account not only speech acts, which are essential, but also other types of communicative acts (Flecha et al, 2020 ). The coercive dominant discourse imposes the link between attraction and violence, influencing the socialization that occurs from birth, in settings such as school, family, circles of friends, and audiovisual products, and therefore prevention is necessary in all of these settings (Aiello et al, 2018 ; Rios-Gonzalez et al, 2018 , 2019 ; Ruiz-Eugenio et al, 2020 ; Villarejo et al, 2020 ).…”
Section: Language and Discourses On Non-hegemonic Masculinities And Self-confidencementioning
confidence: 99%
“…The scientific literature has clarified the influence of first sexual-affective experiences on subsequent sexual-affective relationships [1][2][3][4]. Such first sexual-affective episodes, today, are mostly sporadic relationships [5]. Whereas positive intimate relationships establish a safe emotional base and a positive framework for later relationships [6], toxic sexual relationships have proven to worsen socio-emotional development and physical and mental health [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas positive intimate relationships establish a safe emotional base and a positive framework for later relationships [6], toxic sexual relationships have proven to worsen socio-emotional development and physical and mental health [7][8][9][10][11]. Among these toxic relationships, hookups have been identified as a context with a high prevalence of sexual violence [5,12]. Research in the field of gender violence victimization has shown that nightlife settings, such as discos and bars, are socializing contexts where violent sporadic relationships are the rule [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation